1996
DOI: 10.1080/10407789608913849
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory Phenomena of Low-Prandtl-Number Fluids in a Rectangular Cavity

Abstract: The osci/lalory phenomena in natural conaeaion of low-Prandtl-number fluids were studied numerically in a rectangular cavily with horizontal temperature gradient at Prandtl number Pr = 0.01, aspect ratio A = I, 2, or 4, and Raykigh number Ra = 10', to', or 10'. In the case ofA = IamainstrongroundrollcellwasformedatRa = 10'. Howevtr,atRa = lOs and 10', two secondary roll cells in the core of a main roll cell were formed and rolllled around the center of the system. The flow was oscillating. In the case of A = 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…They demonstrated that at the critical Grashof numbers, periodic oscillations appear in the fluid flow. Kamakura and Ozoe (1996) numerically investigated the oscillatory phenomena in natural convection in a cavity. They considered a law-Prandtl number fluid with Pr = 0.01 and studied the effects of the Rayleigh number and aspect ratio on the fluid flow characteristics such as vortices and oscillatory phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that at the critical Grashof numbers, periodic oscillations appear in the fluid flow. Kamakura and Ozoe (1996) numerically investigated the oscillatory phenomena in natural convection in a cavity. They considered a law-Prandtl number fluid with Pr = 0.01 and studied the effects of the Rayleigh number and aspect ratio on the fluid flow characteristics such as vortices and oscillatory phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the practical importance of transient effects in many enclosure‐natural convection cases present in practice, accounts of this situation are relatively scarce when compared to the steady‐state regime (Lage and Bejan, 1993; Fusegi and Hyun, 1994; Kwak and Hyun, 1996). For an enclosure exposed to a sudden vertical temperature difference, Patterson and Imberger (1980) presented a classical configuration for the transient process, which has then been examined by many other researchers (Yewell et al , 1982; Patterson, 1984; Ivey, 1984; Schladow et al , 1989; Paolucci and Chenoweth, 1989; Schladow, 1990; Paolucci, 1990; Patterson and Armfield, 1990; Armfield and Patterson, 1991; Jeevaraj and Patterson, 1992; Hyun and Lee, 1988; Wakatani, 1996; Kamakura and Ozoe, 1996; Cless and Prescott, 1996; Tagawa and Ozoe, 1996; Chung and Hyun, 1997; Nishimura et al , 1997) taking into account of effects of some parameters such as Prandtl number, temperature‐dependent viscosity, numerical schemes used, wall conduction, temperature‐dependent density. Another scarcity of information in the existing literature is related to boundary conditions different to either a horizontally or a vertically imposed temperature difference, which are often expected to be encountered in practice (Poulikakos, 1985; November and Nansteel, 1987; Ganzarolli and Milanez, 1995).…”
Section: Introductionmentioning
confidence: 99%